Polysaccharides from red seaweeds: Effect of extraction methods on physicochemical characteristics and antioxidant activities - Premarathna, Amal D.; Ahmed, Tamer A.E.; Kulshreshtha, Garima; Humayun, Sanjida; Shormeh Darko, Clarisa Naa; Rjabovs, Vitalijs; Hammami, Riadh; Critchley, Alan T.; Tuvikene, Rando; Hincke, Maxwell T. (Food hydrocolloids, 2024)
Seaweed polysaccharides are reported to possess biological and medicinal properties. Specifically, the antioxidant activity of seaweed extracts is the subject of intensive research due to ever-increasing demands from the food and pharmaceutical industries. The structure and composition of polysaccharides (carrageenan, xylan) extracted from four red seaweed species: Chondrus crispus (CC), Ahnfeltiopsis devoniensis (AD), Sarcodiotheca gaudichaudii (SG) and Palmaria palmata (PP) were compared and correlated with their antioxidant activity. Crude polysaccharide extracts were characterized by NMR (1H and 13C), HPLC-SEC, and FTIR spectroscopy. Total phenolic content (TPC), total sugars, sulfate and protein content were determined using spectrophotometric methods. The antioxidant capacity of each fractionated polysaccharide sample was evaluated by the following methods: DPPH (2,2-diphenyl-1-picrylhydrazyl radical), ABTS (2,2-azino-bis-[3-ethylbenzothiazoline-6-sulfonic acid]), superoxide dismutase (SOD), ferric-reducing power in FRAP (Ferric-reducing Antioxidant Power) assays, and the hydroxyl radical (OH) scavenging capacity assay. The highest antioxidant activity was found in extracts from A. devoniensis (ι/κ hybrid carrageenan), while the lowest was in P. palmata (xylans). Moreover, Chondrus crispus extracts did not possess SOD inhibition activity. Polysaccharides evaluated in this study offer high potential for applications in the food, pharmaceutical and biotechnology industries. [Display omitted] •Polysaccharides (i.e., carrageenan, xylans) extracted from four different red algae were characterized.•Different carrageenan family polysaccharides derived from red seaweeds showed various antioxidant properties.•Xylans extract from Palmaria palmata showed less antioxidant activity.•Chondrus crispus (i.e., CC2B, mixture of several carrageenan-type polysaccharides) have been selected for further studies on fractionation, isolation, and characterization of pure polysaccharides.•The polysaccharide fractions such as mixed carrageenan (i.e., ν-, ι-, and κ-) have the potential for promising biomedical properties (i.e., anti-inflammatory, wound healing).